CD133-Positive Membrane Particles in Cerebrospinal Fluid of Patients with Inflammatory and Degenerative Neurological Diseases - Bobinger, Tobias; May, Lisa; Lücking, Hannes; Kloska, Stephan P.; Burkardt, Petra; Spitzer, Philipp; Maler, Juan M.; Corbeil, Denis; Huttner, Hagen B. (Frontiers in Cellular Neuroscience, 2017)
Background: Analysis of cerebrospinal fluid (CSF) is a frequently used diagnostic tool in a variety of neurological diseases. Recent studies suggested that investigating membrane particles enriched with the stem cell marker CD133 may offer new avenues for studying neurological disease. In this study, we evaluated the amount of membrane particle-associated CD133 in human cerebrospinal fluid (CSF) in neuroinflammatory and degenerative diseases. Methods: We compared the amount of membrane particle-associated CD133 in CSF samples collected from 45 patients with normal pressure hydrocephalus, parkinsonism, dementia and cognitive impairment, chronic inflammatory diseases and 10 healthy adult individuals as controls. After ultracentrifugation of CSF, gel electrophoresis and immunoblotting using anti-CD133 monoclonal antibody 80B258 were performed. Antigen-antibody complexes were detected using chemiluminescence. Results: The amount of membrane particle-associated CD133 was significantly increased in patients with normal pressure hydrocephalus (p<0.001), parkinsonism (p=0.011) as well as in patients with chronic inflammatory disease (p=0.008). Analysis of CSF of patients with dementia and cognitive impairment revealed no significant change compared with healthy individuals. Furthermore, subgroup analysis of patients with chronic inflammatory diseases demonstrated significantly elevated levels in individuals with relapsing-remitting multiple sclerosis (p=0.023) and secondary progressive multiple sclerosis (p=0.010). Conclusions: Collectively, our study revealed elevated levels of membrane particle-associated CD133 in patients with normal pressure hydrocephalus, parkinsonism as well as relapsing-remitting and secondary progressive multiple sclerosis. Membrane glycoprotein CD133 may be of clinical value for several neurological diseases.